Evaluation of the Sustainability of Cash Crop-Based Agroforestry Systems in a Multidimensional Perspective - Adraisna Airansi; Christine Wulandari; Samsul Bakri; Dewi Agustina Iryani; Pitojo Budiono (Jurnal Relevansi : Ekonomi, Manajemen dan Bisnis, 2026)
This study aimed to evaluate the sustainability of commercial crop-based agroforestry systems in Bogorejo Village, Lampung, using a Multidimensional Scaling (MDS) approach. A quantitative approach was used, involving 43 respondents, including farmers and stakeholders. Data were collected through surveys and interviews (October–November 2025) and analyzed using MDS with ordination and leverage techniques across the ecological, economic, social, institutional, and technological dimensions. The ecological dimension was highly sustainable (76.97), while the institutional (70.89), economic (64.84), technological (63.31), and social (56.02) dimensions were moderately sustainable. Sustainability is strongly influenced by deforestation, income trends, mutual cooperation, cooperative involvement, and fertilizer use. The sustainability of agroforestry systems depends on the interaction of ecological, economic, social, institutional, and technological factors, requiring adaptive management strategies focused on sensitive attributes. The study is limited to one village with a small sample size, which restricts generalization. It contributes by providing a multidimensional sustainability assessment and identifying key attributes for policy and sustainable agroforestry management in the region.